Ismāʿīlī - Fāṭimid Legal Education and Judicial Activities in Egypt - Ferda Demir (Dini Araştırmalar)
The Shi’i-Ismāʿīlīs, who established the Fāṭimid Caliphate after conducting long-term missionary activities across the Muslim world, placed significant emphasis on the regulation, teaching, and implementation of law as a fundamental requirement of their rule. This study aims to explain the Ismāʿīlī legal system and the institution of the judiciary within the con-text of Fāṭimid administrative circles, social structure, and spatial organization. To this end, the approaches of state officials and qāḍīs in their judicial activities, as well as the social im-pacts of the law, have been examined through various historical accounts. The data collected has made it possible to explain the judicial activities in relation to the conditions of the time. The study addresses two main topics: the teaching and the application of Ismāʿīlī-Fāṭimid law. The establishment of study circles, the books studied, and the works of key aut-hors, along with the influence of Qāḍī Abu Hanifa al-Nuʿmān b. Muhammad (363/974) and Abu'l-Faraj Ya'qub b. Killis (380/991) on legal education and the judicial system, are promi-nent topics related to Ismāʿīlī legal instruction. The application of Ismāʿīlī law, specifically ju-dicial activities, is another central theme explored in this study. In this context, it is impor-tant to highlight the existing literature on the functioning of the judiciary and the position of qāḍīs during the Fāṭimid period. The study also places particular emphasis on identifying narratives regarding the approaches of statesmen and qāḍīs in judicial activities, as well as examining the social impact of law. This study seeks to offer a thorough analysis of the Ismāʿīlī-Fāṭimid legal system, grounded in historical sources. In doing so, it places emphasis on examining the approaches of state officials and qāḍīs in their judicial activities, as well as the social impacts of the law, as depicted in historical accounts. During the literature review conducted, Ismāʿīlī sources were utilized, benefiting from both primary and secondary sour-ces. The Fāṭimids, who carried out propagation activities for a long time under the da'i system, structured the law and conducted judicial activities in accordance with the princip-les of Ismāʿīlī faith. One of the key indicators is that the qāḍī al-qudāt held a rank higher than that of the da'i. The appointments of qāḍīs were conducted with a specific ceremony, and their areas of responsibility were clearly defined. Additionally, it should be noted that, in the judicial activities of the Ismāʿīlī-Fāṭimid period in Egypt, Sunnī qāḍīs were also appointed alongside Shi’i-Ismāʿīlī qāḍīs as a practice that supported the society's alignment with the government. The focal points of influence in judicial activities underwent changes over time. From the establishment of the state, the judicial influence of certain families and circles re-mained prominent. Over time, as the political influence of the Fāṭimid khalīfahs weakened and administrative functions deteriorated, it became evident that viziers with high authority began intervening in the appointment and responsibilities of qāḍīs in Egypt, thus shaping the judicial system.